A new North American chorus frog species (Amphibia: Hylidae: Pseudacris) from the south-central United States - Lemmon, Emily Moriarty; Lemmon, Alan R.; Collins, Joseph T.; Cannatella, David C. (Zootaxa, 2008)
We describe a new species of chorus frog of the North American treefrog genus Pseudacris from the south-central United States. This new species is morphologically similar to the parapatric species P. feriarum and has thus previously been considered synonymous with this species. The new species is geographically distinct from P. feriarum and from its sister species, P. nigrita. We diagnose the new species based on advertisement call, morphological, and genetic characters.